Targeted gene exchange in plant cells mediated by a zinc finger nuclease double cut. Issue 4 (1st October 2015) - Schneider, Katja; Schiermeyer, Andreas; Dolls, Anja; Koch, Natalie; Herwartz, Denise; Kirchhoff, Janina; Fischer, Rainer; Russell, Sean M.; Cao, Zehui; Corbin, David R.; Sastry‐Dent, Lakshmi; Ainley, W. Michael; et al.
Summary: Genome modification by homology‐directed repair (HDR) is an attractive tool for the controlled genetic manipulation of plants. Here, we report the HDR‐mediated gene exchange of expression cassettes in tobacco BY‐2 cells using a designed zinc finger nuclease (ZFN). The target contained a 7‐kb fragment flanked by two ZFN cutting sites. That fragment was replaced with a 4‐kb donor cassette, which integrates gene markers for selection (kanamycin resistance) and for scoring targeting (red fluorescent protein, RFP). Candidates resulting from cassette exchange were identified by molecular analysis of calli generated by transformation via direct DNA delivery. The precision of HDR‐mediated donor integration was evaluated by Southern blot analysis, sequencing of the integration locus and analysis of RFP fluorescence by flow cytometry. Screening of 1326 kanamycin‐resistant calli yielded 18 HDR events, 16 of which had a perfect cassette exchange at the insert junction and 13 of which produced functional RFP. Our results demonstrate that ZFN‐based HDR can be used for high frequency, precise, targeted exchange of fragments of sizes that are commercially relevant in plants.